Search for Pure Leptonic B Decays at ATLAS and CMS - Gaur, Bakul (arXiv.org, 2013)
The rare decays \(B_{s,d}^0 → μ^+μ^-\) are important probes for new physics beyond the Standard Model. These decays are subjects of studies at the LHC. The ATLAS and CMS collaborations have analyzed the proton-proton collisions data at 7 TeV centre-of-mass energy collected in the year 2011. They have established upper limits on the branching fractions of the two decays. This paper presents a report.